Chapter 6 Apprenticeship Learning in Preparation for Meeting the Unforeseen - Nyhus, Ingrid (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The chapter analyzes teaching where the goal is to enable students at the Armed Forces Staff College to master unforeseen events. The students are all participants in a program for joint operations in which different military branches are placed together to solve complex tasks. How can the supervisor contribute to increased samhandling when facing the unforeseen? The goal is for students to be able to cope with the roles that exist in a normal NATO headquarters and to learn how to use NATO's operational planning strategy. The group supervisor becomes a form of master who greatly influences the approach of students to the training community. From a sample of one hundred students, five groups consisting of four to five students of both sexes, with varied defense-force affiliations, backgrounds and experience were selected to be interviewed. A total of 23 informants participated in the interviews. In addition, observations were carried out. Apprenticeship Learning as a method is appropriate to prepare the students better for samhandling in anticipation of the unforeseen. The way the supervisor manages his or her role has a great deal of impact on samhandling and learning outcomes. The supervisor's insight and expertise in what is needed to make groups work together is decisive. Strengthening and developing samhandling in exercises is a suitable educational method for military forces in meeting unforeseen events, provided that it is done properly."